2023
DOI: 10.3390/ijerph20043497
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Environmental Uncertainties and Strategic Flexibility in Innovation Activities on NEV Battery Recycling Firms in China

Abstract: Due to the popularization and development of new energy vehicles (NEVs) worldwide, power batteries that have been used are being retired and replaced. In China’s battery recycling industry, the legal NEV battery recycling enterprises are at a negative financial performance. Based on theory of organizational adaptation, the key to innovation performance and sustainable development is recognition of the environment and strengthening organizational flexibility. This study empirically explores the bidirectional dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 71 publications
(80 reference statements)
0
0
0
Order By: Relevance
“…At any stage of the life cycle, enterprises are subject to the limitations of a complex environment [4] .Some studies have found that environmental uncertainty pushes firms forward, increasing R&D investment and stimulating open innovation to enhance their strengths in order to be competitive in the marketplace [1,5] .…”
Section: Firms' Business Conditions Environmental Uncertainty and Fir...mentioning
confidence: 99%
“…At any stage of the life cycle, enterprises are subject to the limitations of a complex environment [4] .Some studies have found that environmental uncertainty pushes firms forward, increasing R&D investment and stimulating open innovation to enhance their strengths in order to be competitive in the marketplace [1,5] .…”
Section: Firms' Business Conditions Environmental Uncertainty and Fir...mentioning
confidence: 99%